2019
DOI: 10.5935/2359-4802.20190077
|View full text |Cite
|
Sign up to set email alerts
|

Association between Therapeutic Adherence and the Profile of Patients with Resistant Hypertension

Abstract: Background: Resistant hypertension (RH) consists of increased blood pressure (BP) despite the use of 3 or more antihypertensives or BP control only when is use of 4 or more antihypertensives. It is fundamental to exclude pseudoresistance, which can be attributed to poor therapeutic adherence. Adherence evaluation, generally by the Morisky-Grenn test, is important because, when appropriate, it is associated with fewer cardiovascular complications and better BP control. Objectives: To evaluate the adherence of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…21 Uncontrolled blood pressure has been frequently associated with low treatment adherence. 3,22 Araújo & Aras Junior 23 reported that most of their studied patients had uncontrolled hypertension, regardless of treatment adherence. However, the authors observed an expected trend: patients with controlled hypertension had good treatment adherence, and most of patients with uncontrolled hypertension had poor adherence.…”
Section: Original Articlementioning
confidence: 94%
See 1 more Smart Citation
“…21 Uncontrolled blood pressure has been frequently associated with low treatment adherence. 3,22 Araújo & Aras Junior 23 reported that most of their studied patients had uncontrolled hypertension, regardless of treatment adherence. However, the authors observed an expected trend: patients with controlled hypertension had good treatment adherence, and most of patients with uncontrolled hypertension had poor adherence.…”
Section: Original Articlementioning
confidence: 94%
“…The patient was instructed about the correct use of medication, and blood pressure levels were normalized after that. However, according to Araújo & Aras Junior, 23 although the Morisky-Green test is the most used method to quantify adherence to anti-hypertensive treatment in Brazil, enabling comparison between studies, the instrument may not be the most appropriate considering its low sensitivity (43.6%).…”
Section: Original Articlementioning
confidence: 99%
“…This issue of the International Journal of Cardiovascular Sciences presents the results of the study entitled "Association between Therapeutic Adherence and the Profile of Patients with Resistant Hypertension", by Araújo and Aras Junior. 6 The study was conducted with hypertensive patients seen in an outpatient clinic of a university hospital in Brazil and adds to the knowledge about the management of resistant hypertension in our country. 6 The study brings encouraging results, showing that 83% of patients had good adherence to treatment, maybe because they were seen in a tertiary health care institution.…”
mentioning
confidence: 99%
“…6 The study was conducted with hypertensive patients seen in an outpatient clinic of a university hospital in Brazil and adds to the knowledge about the management of resistant hypertension in our country. 6 The study brings encouraging results, showing that 83% of patients had good adherence to treatment, maybe because they were seen in a tertiary health care institution. Twenty percent of patients had pseudoresistant hypertension and 17% refractory hypertension (patients with uncontrolled hypertension even taking five or more antihypertensive drugs).…”
mentioning
confidence: 99%
See 1 more Smart Citation